(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the present study was to evaluate exclusive breastfeeding (EBF) rates and breastfeeding duration in adolescent Turkish mothers after term-uncomplicated deliveries.Material and Methods: The study comprised 803 uncomplicated, nulliparous women, who had a single pregnancy and delivered at term gestational age. After excluding any maternal and fetal factors that affected early breastfeeding initiation, 674 nulliparous pregnant women were divided into three groups as follows: adolescents 16–17 years old, adolescents 18–19 years old, and non-adolescents 20–24 years old. The primary outcome of the study was defined as EBF of the infant, especially during the first 6 months of life. Results: Gestational age at delivery, birth weight, newborn gender, rate of induced labor, and rate of vaginal deliveries were similar among the groups. We found that 22.5% (14/62) of patients in the 16- to 17-year group, 41.8% (72/172) in 18- to 19-year group, and 72.9% (321/440) in the 20- to 24-year group had EBF during the first 6 months of their baby’s life. The rate of EBF during the first 6 months was significantly less in the 16- to 17-year and 18- to 19-year groups compared to that in the 20- to 24-year group (p0.001). The mean breastfeeding duration was 6.7±1.4months in the 16- to 17-year group, 9.5±2.2 months in the 18-to 19-year group, and 15.2±3.2 months in the 20-to 24-year group. Mean breastfeeding duration was significantly less in the 16-to 17-year and 18- to 19-year groups than in the 20- to 24-year group (p0.001).Conclusion: Our results indicated that adolescent pregnancy in Turkish populations is an important risk factor affecting both EBF during the first 6 months of life and breastfeeding duration.